Planning national adaptation responses to climate change - Georgis, K. (2015)
Climate change research must be nationally relevant for research outputs to be used broadly. This is why CIMMYT-CCAFS conducted its research in close collaboration with the Ethiopian Institute of Agricultural Research (EIAR) and other stakeholders in Ethiopia. The climate research outputs generated were used as inputs during the development of Ethiopia’s National Climate Change Adaptation Strategy. The collaboration with national stakeholders also helped in building national climate research capacity in Ethiopia where climate change information is limited.